Primary and pre-primary teacher initial education and training in Bergamo in the European context: feature and challenges - Cristina Casaschi (Firenze University Press, 2018)
Primary and pre-primary teacher's initial education and training is a strategic focus for a country's development prospect, as generally highlighted on international scale. It is a powerful personal pedagogical opportunity as well as a social responsibility as training can also be a personal self-education chance when organized in an integrated way. This essay is clearly showing the way University of Bergamo has taken on this challenge and what it is putting in place as answers in terms of work-based learning paradigma: academic procedures, organization and educational side. La formazione dell'insegnante di scuola dell'infanzia e primaria a Bergamo nel quadro del contesto europeo: peculiarità e sfide La formazione dell'insegnante di scuola dell'infanzia e primaria è, come sottolineato a livello internazionale, uno snodo strategico per le prospettive di sviluppo di un Paese. Oltre che una responsabilità sociale, è anche una potente opportunità pedagogica personale in quanto la preparazione alla professione può essere, se impostata in modo integrato, occasione di autoformazione della persona. Il contributo presenta come l'Università degli Studi di Bergamo abbia accolto questa sfida e quali risposte di carattere ordinamentale, organizzativo e didattico, riassumibili nel paradigma dell'alternanza formativa, stia mettendo in campo.